Gene manipulation applications in autoimmune diseases 2 - Ferreira, Leonardo M. R. (Henry Stewart Talks, 2026)
Chimeric antigen receptor (CAR), Islet transplantation for T1D treatment, Treating T1D using islet transplant and CAR Tregs, Genetic modifications of human Treg, Reprogramming human Treg specificity